In Vivo Comparative Study of Different Dosage Forms of Baclofen - Ali, Bassam Abduh (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study to compare the relative bioavailability of baclofen as a peroral tablet with the new formulations (transdermal and buccal films). Materials and Methods: Rapid and simple high-performance liquid chromatography/ultraviolet method has been adopted and validated for the determination of baclofen in human plasma with acceptable linearity, precision and accuracy. The study was performed on six human volunteers divided into three groups each contained two individuals. The first group was dosed with 20 mg of baclofen tablet (Lioraz®) as a reference, the second group received 40 mg baclofen transdermal film, and the third group received 20 mg baclofen buccal film. Transdermal and buccal films were subjected to in vivo study to evaluate the bioavailability parameters and then compared to the reference. Results and Discussion: Following Lioraz® tablet, the maximum concentration was achieved after 3.0 h unlike, after transdermal film with a double dose, it was at 6.0 h whereas, following buccal film, maximum time was 3.0 h post-dosing. Thus absorption from buccal films was faster, whereas transdermal spent longer times to reach the maximum concentration in systemic circulation. The mean values of pharmacokinetic parameters were significantly higher from transdermal than oral, demonstrating prolongation of baclofen action, whereas with buccal was lower. Taking Lioraz® as a reference, the % relative bioavailability from transdermal and buccal film was 78.99% and 89.22%, respectively. Conclusion: Study indicates that the absorption from buccal films was faster, whereas the transdermal spent longer times to reach the maximum drug concentration. Transdermal film of baclofen was successful in all the established studies by improving the prolongation of action and increasing the half-life of baclofen.